Periodic Solutions for Autonomous (𝑞,𝑝)-Laplacian System with Impulsive Effects - Xiaoxia Yang; Haibo Chen (Journal of Applied Mathematics)
By using the variational method, some existence theorems are obtained for periodic solutions of autonomous (𝑞,𝑝)-Laplacian system with impulsive effects.